2020
DOI: 10.1101/gad.337287.120
|View full text |Cite
|
Sign up to set email alerts
|

Replication stress conferred by POT1 dysfunction promotes telomere relocalization to the nuclear pore

Abstract: Mutations in the telomere-binding protein POT1 are associated with solid tumors and leukemias. POT1 alterations cause rapid telomere elongation, ATR kinase activation, telomere fragility, and accelerated tumor development. Here, we define the impact of mutant POT1 alleles through complementary genetic and proteomic approaches based on CRISPR interference and biotin-based proximity labeling, respectively. These screens reveal that replication stress is a major vulnerability in cells expressing mutant POT1, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 91 publications
5
41
0
Order By: Relevance
“…The dependency on the nuclear periphery for repair of heterochromatic DSBs appears analogous to the repair of persistent DSBs or collapsed replication forks in budding yeast, which also require the SUMOylation pathway to coordinate movement to the nuclear periphery [ 94 ]. Although the movement of heterochromatic DSBs to the nuclear periphery has not been described in mammalian cells to date, two recent studies have revealed that stressed-replication foci and dysfunctional telomeres can associate with the nuclear periphery in human cells [ 95 , 96 ]. Moreover, nuclear pore stability was found to be important to prevent telomere fragility, indicating the essentiality of the nuclear periphery in the maintenance of repetitive telomeric regions in humans [ 95 ].…”
Section: Constitutive Heterochromatinmentioning
confidence: 99%
“…The dependency on the nuclear periphery for repair of heterochromatic DSBs appears analogous to the repair of persistent DSBs or collapsed replication forks in budding yeast, which also require the SUMOylation pathway to coordinate movement to the nuclear periphery [ 94 ]. Although the movement of heterochromatic DSBs to the nuclear periphery has not been described in mammalian cells to date, two recent studies have revealed that stressed-replication foci and dysfunctional telomeres can associate with the nuclear periphery in human cells [ 95 , 96 ]. Moreover, nuclear pore stability was found to be important to prevent telomere fragility, indicating the essentiality of the nuclear periphery in the maintenance of repetitive telomeric regions in humans [ 95 ].…”
Section: Constitutive Heterochromatinmentioning
confidence: 99%
“…In addition, caPOT1 mutations have been studied in human cells either by overexpression of caPOT1 alleles combined with and without the simultaneous depletion of wild-type POT1 in cancer cells or by engineering the homozygous mutations in cancer cell lines (Pinzaru et al, 2016;Chen et al, 2017;Gu et al, 2017;McMaster et al, 2018;Pinzaru et al, 2020). Under these conditions, POT1 mutations lead to telomere elongation and telomere deprotection.…”
Section: Introductionmentioning
confidence: 99%
“…In human cells, cancer-associated mutant alleles of the telomere protein POT1 promote telomere-specific replication stress [60]. Complementary whole genome CRISPR interference and proximity-ligation proteomic screens revealed that replication stressed telomeres in mutant POT1 expressing cells associated with subunits of the NPC Y complex, nuclear basket, and NUP62 subcomplex [61]. Preventing POT1 mutant telomeres from associating with NPCs altered the type of DNA repair reactions that occurred at chromosome ends, consistent with specific DNA repair mechanisms ongoing at the nuclear periphery [61].…”
Section: Npcs and Dna Repairmentioning
confidence: 99%
“…Examination of replication stressed human telomeres in mutant-POT1 cells revealed that inhibiting actin-dependent telomere relocalization to NPCs increased telomere fragility [61], which is a marker of telomere replication stress [55]. Further, preventing telomere-NUP interactions elevated telomere sister chromatid exchange (T-SCE) [61], signifying an increase in conventional telomere HDR events [72].…”
Section: Sumoylation Regulates Dna Repair At Npcsmentioning
confidence: 99%